Basic Medical Emergency Treatment for Maxillofacial Injuries - Ilirian Lenjani; Fatime Lenjani; Mentor Mustafa; Agron Dogjani; Basri Lenjani (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Maxillofacial trauma presents unique challenges due to the complex anatomy of the face, encompassing vital structures. Beyond physical injuries, these cases significantly impact a patient's appearance and function, necessitating a multidisciplinary approach.